Investigating Relationship of positive Family Historypattern and the incidence of idiopathic epilepsy in patients with epilepsy - Masoud Ghiasian; sajjad Daneshyar; Elham Khanlarzadeh; Mohamadreza Bolouri Novin (Babol University of Medical Sciences, 2020)
Background: Epilepsy is one of the most common neurological disorder. This study aimed to investigating the relationship of family history pattern and prognosis of idiopathic epilepsy. Methods: In this study, 377 patients with epilepsy referring to Imam clinic were investigated. Data were collected by means of a checklist that contained demographic data, age of first seizure attack, response rate to treatment, parental relationship, seizure history, family history and recurrence of seizure. And then the data were analyzed by SPSS Version 23. Results: Among the 337 patients, 199 (52.8 %) individuals were males and 178 (47.2%) individuals were females. The mean age of patients was 28.3±14 years. Approximately 50% of patients had a history of seizure and epilepsy in one of the close first relatives or relatives who had adequate knowledge of their disease. The mean incidence age of epilepsy was lower in patients with a positive family history of disease than those who did not have a family history of epilepsy (p<0.05). Among the 33 patients who did not respond well to treatment, there was a 75% family history of epilepsy (p<0.05). The average age of epilepsy was lower in those with family marriage, but was not statistically significant. Conclusion: According to the findings of the present study, the patients diagnosed with idiopathic epilepsy, the family history of epilepsy and seizure, especially in their first degree relatives is fairly high, that may indicate genetic causes in the etiology of the disease.